Men and women in rice farming in Africa: A cross-country investigation of labor and its determinants - Medagbe, F. M.K.; Komatsu, S.; Mujawamariya, Gaudiose (Frontiers Media, 2020)
Women make significant contribution to rice farming, processing, and marketing, but only have limited access to technical knowledge and technologies that can reduce their drudgery and labor bottlenecks, and provide them with additional income. Women also oversee the reproductive responsibilities. This paper comparatively investigates the role of women in rice farming across four countries (Burkina Faso, Côte d’Ivoire, Madagascar, Sierra Leone) by examining the labor time distribution and its resulting income for men and women. It also assessed the determinants of their labor inputs in different rice farming environments. Results show that women and men spend on average 1 to 3 hours per day in rice production, making 45 to 135 working days of involvement in annual rice cultivation. Looking into the distribution of labor input provision in productive activities, it is found that apart from the specific activity of rice parboiling, which is practiced in certain countries mostly by women, men are the ones more engaged in rice farming. The specific labor input depends on several factors including the farm size, time spent on non-agricultural activities, and access to production equipment. These results provide the first evidence to that women farmers do not necessarily spend more time than men in rice cultivation in Africa, as it is often assumed. Certainly, across countries and systems, and also within male and female farmers categories, there are heterogenous labor inputs and associated determining factors and incomes. Male farmers earn higher income than female farmers in the different productive activities, except only for rice parboiling. This finding indicate that increasing labor input for rice would not result in higher income for female farmers. Female farmers might find better options by other agricultural activities such as food processing.